Forgiveness among mothers of female adolescents who experienced unwanted pregnancy - Mohammad Adi Ganjar Priadi; Gurmichele Gurmichele (Universitas Ahmad Dahlan, 2019)
Unwanted pregnancy is an issue that affects, not only the individual who got pregnant, but also their mothers. Such a traumatic experience may cause psychological distress in these mothers, affecting their overall psychological well-being. This study aimed to explore the process of maternal forgiveness experienced by mothers in dealing with their children who had unwanted pregnancy. Qualitative method was applied in this research. Participants were selected by purposive sampling technique. Three mothers of young women who experienced unwanted pregnancy participated in this research. The results highlight the forgiveness process experienced by three participants. Forgiveness process start with negative emotion of the mothers, followed by giving empathy to her daughter as part of the forgiveness process. Self contemplation plays a crucial role on mothers’ transition from feeling negative emotions to giving emphaty to their daughters.